Reporting Disasters : Famine, Aid, Politics and the Media. - Franks, Suzanne (Hurst, 2014)
The media reporting of the Ethiopian Famine in 1984-5 was an iconic news event. It is widely believed to have had an unprecedented impact, challenging perceptions of Africa and mobilising public opinion and philanthropic action in a dramatic new way. The contemporary international configuration of aid, media pressure, and official policy is still directly affected and sometimes distorted by what was--as this narrative shows--also an inaccurate and misleading story. In popular memory, the reporting of Ethiopia and the resulting humanitarian intervention were a great success. Yet alternative int.